Handbook of Sustainability in Additive Manufacturing Volume 2 - Muthu, Subramanian Senthilkannan; Savalani, Monica Mahesh (Environmental Footprints and Eco-design of Products and Processes, 2016)
This book highlights essential aspects of sustainability in the Additive Manufacturing (AM) field in two separate volumes. It demonstrates the details of this technology and examines its implications for sustainability throughout the entire product life cycle, embedded carbon, and future research efforts that will be necessary to move this technology towards sustainable mainstream production. Sustainability is nothing new for any industrial field, and AM is no exception. Accordingly, industrialists and scientists alike are intensively engaged in research to promote sustainability in this important field.